Como você está? princípios da comunicação não-violenta permeabilizando relações - Consorte, Pedro Leme (2020)
This research was born from the need to problematize aspects of contemporary society, such as, for example, the benefits of technological advances, calling attention to the importance of the side effects that they embody, and to reflect, in the light of the Nonviolent Communication, on the possible new kinds of violence that are being naturalized in the neoliberal context. In the hyperconnected society (Society 5.0), allied to capitalism and the culture of consumption, changes in people’s habits were produced and relations were being waterproofed. The hypothesis was that the current latent logic, which is based on a moralizing duality of relationships, ended up waterproofing relationships and fomenting violence. The theoretical foundation, supported mainly by Dardot and Laval (2016; 2017), Boltanski (2009), Foucault (1987), Benjamin (2011), Agamben (2011), Pinker (2012; 2018), Marshall Rosenberg (2006; 2015) , Carl Rogers (2009), David Bohm (2005), Jean-Marie Muller (2007), Johan Galtung (1969), Paulo Freire (2014), and Katz and Greiner (1998, 2006), allowed for their support and development. The understanding of the body that guided the investigation was the concept of corpomedia (Katz and Greiner). However, in the last semester of the research, the pandemic produced by COVID-19 was installed, which radically transformed the previous form of communication, and explained the profound inequality that founds Brazilian society. This investigation will not seek to explore the emergence of new communication phenomena more recent in their complexity, but it will not shy away from registering their importance, as is the case for an academically active researcher in the area of communication. Of a qualitative nature, here bibliographic review and materials were gathered as a result of empirical observations, reports and testimonies from the practices of experiences and workshops that used dynamics of Nonviolent Communication (Rosenberg), and were carried out in Brazil, Italy, Greece, and in England, between January 2018 and March 2020. Reassessing them now, in this other moment of production of violence in the pandemic, is a task that imposes itself as a continuity to what is presented here